NASAL ASSIMILATION AND SUBSTITUTION IN STANDARD INDONESIAN: EVIDENCE FROM LOANWORDS PRODUCTION TASK - Ferdinan Okki Kurniawan (Masyarakat Linguistik Indonesia, 2016)
This paper investigates nasal assimilation and substitution in Standard Indonesian (SI). In SI, the verbal prefix /məN-/ alternates in its shape at the prefix-root boundary when it is combined with root-initial obstruents. This study examines loanword roots borrowed from Arabic, Portuguese, Dutch and English. Using a speech production task, this investigation finds patterns of variation which are conditioned by inter- and intra-speaker differences, and place of articulation. This study proposes to model the patterns of variation in Noisy Harmonic Grammar (NHG; Coetzee and Kawahara 2013, Coetzee and Pater 2011).